Until August - García Márquez, Gabriel, 1927-2014 (Alfred A. Knopf, 2024)
In a rediscovered novel from the Nobel Prize-winning author of One Hundred Years of Solitude, Ana Magdalena Bach has been happily married for 27 years, and yet, every August, she travels by ferry to the island where her mother is buried, and for one night takes a new lover.